A Placemaking Approach to Assessing the Resilience of the Kelompok Tani Jambu, Gemblakan Atas Kampong - Hartono, Steffany; Wiyatiningsih; Prasetyo Utomo, Gregorius Sri Wuryanto (Departement of Architecture, Universitas Islam Indonesia, 2024)
Gemblakan Atas Kampong, Suryatmajan, is one of the kampongs in the Malioboro area that produces processed guava products marketed at culinary festivals in Yogyakarta City. Kelompok Tani Jambu conducts the production process on one of the kampong roads. The road, which initially functioned as a circulation route, has changed its function to become a production space for processed guava. The change in the function of the kampong road has the potential to cause conflicts of interest between kampong. Based on this background, this study aims to identify social interactions between residents and Kelompok Tani Jambu on the kampong road used as a production space for processed guava. Placemaking will be used as a theoretical framework to assess the resilience of the Gemblakan Atas community, Suryatmajan. The identification of the placemaking process uses a table that crosses the characteristics of placemaking with space interfaces related to social interaction in public spaces. Community resilience is measured based on the social and physical capital owned by Kelompok Tani Jambu. The results showed that the residents of Gemblakan Atas kampong and Kelompok Tani were actively involved in forming a public production space on the kampong street. The production space formed by Kelompok Tani Jambu got a good response from the community. This is the physical and social capital of the resilience of Kelompok Tani Jambu, Gemblakan Atas Kampong. Keyword: Kelompok Tani Jambu; Gemblakan Atas Kampong; Placemaking; Space Interface; Sustainable Livelihood Frameworks